WORK FROM HOME SETTING EXPECTATIONS FOR THE FUTURE OF WORK – THE HYBRID MODEL - LAKSHAY, SACHDEVA (2022)
"Work from Home" is not a new term in today's world. It has been around for more than a decade. The COVID-19 pandemic has forced everyone across the world to work remotely. This concept is represented in various ways by the term; telecommuting or remote work. Either way, the COVID-19 pandemic appeared suddenly, making this a drive rather than a choice. The study focuses on corporate employees and culture. Since the pandemic has completely changed the way businesses use to work, it is of utmost importance to look at the current Work from Home situation and its impact and how it’s leading to the hybrid model, the future of work. The main research revolves around the reasons behind the employee selection between working from home (current scenario), working from an office (pre-covid-19), or a hybrid model (post/during covid-19)? What is the rationale and expectation behind the decision? This study endorses the qualitative research method. For that purpose, twelve corporate employees were interviewed using open-ended questions. The data is processed through thematic analysis and coding method and a rational comparison is conducted between the research findings, discussion and literature. With the assistance of appropriate examination and study, it’s found that the surge in interest in hybrid work models can be interpreted as a reflection of how past concepts of "normal" are currently being rebooted. Individuals and organizations, for various reasons, do not wish to return entirely to pre-COVID ways of working. Instead, they're reimagining the next "normal" and rethinking the best ways to work.